Lice Infestation in the Soviet Army During the Second World War: A Personal Account - Appenzeller, Otto (British Journal of Healthcare and Medical Research, 2024)
During the Second World War, the Soviet Army faced numerous challenges, including the pervasive issue of lice infestation among its troops. This paper investigates the epidemiology of lice infestation, its impact on soldiers’ health and morale, and the measures implemented to control and prevent its spread. Through historical analysis and medical records, this study highlights the significant role that lice played in the daily lives of soldiers and the efforts made to mitigate this health threat amidst wartime conditions. I draw here attention to a method to get rid of the lice not tried before but very effective and simple to use. Simply bury clothing full of lice in a hole in the earth; leave a bit of the shirt above ground. The lice will collect above ground; cut off the shirt edge and burn it.